CORRELATION AND PATH COEFFICIENT ANALYSIS FOR GRAIN YIELD IN AEROBIC RICE (Oryza sativa L.) GENOTYPES - D. SRINIVASA CHARY; S. SUDHEER KUMAR, A. SRIJAN, KULDEEP SINGH DANGI, P. SENGUTTUVEL, R. M. SUNDARAM (The Journal of Research, PJTSAU, 2019)
As rice is the staple food in most parts of India, to feed the increasing population there is a great need to increase production of rice and productivity of land under rice cultivation. In Asia, about 17 million ha of irrigated rice area may experience â€œPhysical water scarcityâ€ and 22 million ha may have â€œEconomic water scarcityâ€ by 2025 (Tuong and Bouman, 2003). Therefore, efficient use of water is required in rice production. Aerobic rice is one such new concept to decrease water requirement in rice production (Vijayakumar, 2006). However, crop yield is the end product of the interaction of a number of other interrelated attributes. The efficiency of selection for yield mainly depends on the direction and magnitude of association between yield and its component characters and also among themselves. Correlation gives only the relation between two variables whereas path coefficient analysis allows separation of the direct effect and their indirect effects through other attributes by partitioning the correlations (Wright, 1921). In this study an attempt was made to identify the major contributing characters for grain yield, their direct and indirect effects.